Cosmetic Surgery and Female Printing Press. The Pedagogical Formation of the Competent Patient - Córdoba, Marcelo (2018)
Aesthetic surgery is a complex, multiple and heterogeneous phenomenon: at the same time medical practice, beauty practice and consumer practice. This complexity justifies its being understood as a "technology of gender"". In this article I discuss some of the ways in which the practice of aesthetic surgery is framed by −and contributes to (re)produce− certain representations of gender, focusing on women’s magazines. In particular, I analyze the variants of the pedagogical function that are manifested in the discourse of a magazine focused in medical beautification practices. For these purposes, I apply the principle of modalization developed within the framework of the narrative grammar of structuralist semiotics."